Health professions education in Serbia: Evaluation and measures for quality improvement through experiential education, interprofessional education and teaching competencies development - Kovačević Milena; Odalović Marina; Đukić-Ćosić Danijela; Vasiljević Dragana; Parojčić Jelena; Tasić Ljiljana (Vojnosanitetski Pregled)
Background/Aim. Health professions education is facing emerging issues. A comprehensive situation analysis was performed among academic staff, healthcare practitioners, and healthcare science students to address and respond to new trends. The aim of the study was to investigate the attitude, perception, and the recognized needs towards experiential education (EE), interprofessional education (IPE), and teaching competencies development (TCD). The critical evaluation of the existing quality standards for further quality improvement in health professions education in Serbia was provided. Methods. The survey on EE, IPE, and TCD was conducted within the Reinforcement of the Framework for Experiential Education in Serbia (ReFEEHS) project, co-funded by the Erasmus+ program of the European Comission at four Serbian universities (the University of Belgrade, the University of Kragujevac, the University of Niš, and the University of Novi Sad). Four task groups were appointed to perform a desk review of the existing curricula, recommendations, and practices within each of the four health professions education (Medicine, Pharmacy, Dentistry, and Nursing) in Serbia and assess the level of compliance with relevant educational policies and practices in the European Union. Results. A total of 1,507 respondents completed the survey. A highly expressed positive attitude was found towards EE, IPE, and TCD among all the respondents. The majority of the respondents (> 70%) shared that EE should be organized in real-life practice and involve students’ work under the supervision of a qualified supervisor, as well as interactions with patients and healthcare professionals. About 90% of the respondents supported the inclusion of IPE teaching activities into EE, with 77% of students expressing high motivation to attend those classes, whereas 93% of academic staff was eager to deliver and teach joint IPE subjects. Only 20% of academic staff has already attended some TCD program, while 75% recognized the need for its organization. Moreover, 90% of healthcare practitioners have recognized that mentors/clinical supervisors also need additional skills for effective mentoring work within health science education. Based on the survey results, recommendations for improvement were given within three educational fields, healthcare science curricula, professional practice (traineeship), teaching staff, and regulations. Conclusion. The results derived from the survey served as a starting but also a vital point for higher education improvement in Serbia. All interested parties – academia, students, healthcare professionals, and regulatory bodies should collaborate on achieving improved, contemporary, and transformative health professions education.